MODIFIKASI KAPAL PURSE SEINE 30 GT DENGAN MENAMBAHKAN CADIK UNTUK MENINGKATKAN SURVIVAL OF INTACT STABILITY - Hasanudin, Hasanudin; Yulianto, Totok; Ariesta, Rizky Chandra (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2019)
A fishing operation is a dangerous and high risk activity. Stability of the vessel plays an important role in performing safely and successfully fishing operations. A brand new 30 GT purse seiner, production of a traditional shipyard in Batang Regency, experienced 15o heel after its launch. This condition potentially affects the stability of the vessel. The purpose of the study is to analyze the vessel stability and improve existing stability by adding outriggers. Research was conducted in two phases, data collection in the research site and stability analysed using a naval architecture software. The vessel stability was analyzed in six loading scenarios following the fishing operation process, subsequently the stability was compared against IMO standard. Results show that with the existing design, the vessel does not meet IMO criteria for the most applied scenarios. Next step, outriggers were added in both sides of the vessel model, as an effort to improve its stability. Accordingly, it is revealed that outriggers addition is scientifically proven to improve the stability of the studied vessel. As this research merely focused on the stability improvement, further analysis regarding maneuverability is required given a purse seiner operates encircled fishing gear.Keywords: outrigger, purse seiner, stability